2007
DOI: 10.1186/1471-2164-8-122
|View full text |Cite
|
Sign up to set email alerts
|

Phase variation and microevolution at homopolymeric tracts in Bordetella pertussis

Abstract: Background: Bordetella pertussis, the causative agent of whooping cough, is a highly clonal pathogen of the respiratory tract. Its lack of genetic diversity, relative to many bacterial pathogens, could limit its ability to adapt to a hostile and changing host environment. This limitation might be overcome by phase variation, as observed for other mucosal pathogens. One of the most common mechanisms of phase variation is reversible expansion or contraction of homopolymeric tracts (HPTs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 51 publications
(74 reference statements)
0
36
0
2
Order By: Relevance
“…The genome of the derived species, pertussis and parapertussis , has a smaller size than their ancestor with a considerable increase in the number of IS elements, pseudogenes and many chromosomal rearrangements more particularly for B. pertussis . It was also recently shown that allelic polymorphism at homopolymeric tracts is common within the B. pertussis genome [16]. This polymorphism could play a role in the adaptation of B. pertussis to the Human host but could also play a role for evasion of the immune system.…”
Section: Discussionmentioning
confidence: 98%
“…The genome of the derived species, pertussis and parapertussis , has a smaller size than their ancestor with a considerable increase in the number of IS elements, pseudogenes and many chromosomal rearrangements more particularly for B. pertussis . It was also recently shown that allelic polymorphism at homopolymeric tracts is common within the B. pertussis genome [16]. This polymorphism could play a role in the adaptation of B. pertussis to the Human host but could also play a role for evasion of the immune system.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, evidence from clinical studies may suggest that the Fim antigens are perhaps being subjected to immune selection due to vaccine-induced and natural-antibody-driven adaptation (Gogol et al, 2007;Tsang et al, 2004). The sophisticated controls used by B. pertussis to regulate virulence genes (differential binding of the BvgA~P activator to the promoters, different RNAP/activator architectures and phase variation by programmed mutation) demonstrate how a pathogen that is highly clonal and lacks the genetic diversity of many other pathogens can be quite successful as an obligate human pathogen (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One benefit of phase variation is that it allows an organism to create diversity in an otherwise clonal population -a valuable trait for B. pertussis which has unusually poor genomic diversity for a pathogen (Gogol et al, 2007). Phenotypic diversity among surface-exposed adhesins is no doubt important for evading the host surveillance system and may be important to ensure some bacteria are poised to move to a new environment through detachment and shedding (Dybvig, 1993;Henderson et al, 1999).…”
Section: Phase Variation In the Fim Genes Generates Phenotypic Diversmentioning
confidence: 99%
“…The LDR products are separated in capillaries and the ligation occurrence is visible due to the band-shift. The use of various probe sets simultaneously is still possible and the ligated probes can be separated with a one base pair resolution [17,46]. This approach can be cost effective, but when the simultaneous visualization of many different DNA species or a higher sensitivity is needed UAs are more convenient.…”
Section: Ligation Detection Reaction-universal Arrays (Ldr-ua)mentioning
confidence: 99%